Sistem Pendukung Keputusan Oemilihan Beras Berkualitas di Perum Bulog Kanwil Riau dan Kepri Menggunakan AHP Berbasis Web - Dhia Salsabila Yazmi; Dedi Rohendi; Aulia Zikri Rahman (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The current quality rice selection process at the Riau and Riau Islands Regional Office of the State Logistics Agency (Bulog) remains time-consuming and potentially subjective due to its reliance on manual inspections and supplier history. To address this, an objective, systematic, and measurable web-based Decision Support System (DSS) was developed. This study employed a Research and Development (R&D) method with a Waterfall model, encompassing analysis, design, implementation, and testing. Evaluation of rice alternatives was conducted using the Analytical Hierarchy Process (AHP) method based on five criteria: moisture content, milling degree, coarse grains, broken grains, and pH level. The developed system successfully weighted the criteria and automatically ranked the rice. Through Black Box Testing, the system achieved a 100% success rate, proving its functionality. This DSS has proven to accelerate, standardize, and structure the quality rice selection process to support decision-making at Bulog.